KINERJA PORTOFOLIO SAHAM BERDASARKAN STRATEGI PEMILIHAN SAHAM DI BURSA EFEK INDONESIA - Maya Sari, Dewi Fitma; Wiksuana, I Gusti Bagus; Purbawangsa, Ida Bagus Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
Determination of optimal portfolio can be done with diversification strategy or concentration strategy. One of concentration strategy followers is Warren Buffet,.The objective of this research is to find out the difference between the portfolio performance which is formed based on Warren Buffet’s strategy and stock portfolio which is formed based on LQ45 index. This research formed seven ( 7 ) stock portfolios which is formed using Markowitz method and measured using Sharpe’s method. The technique of data analysis used is t-test. The result of this research shows that the performance of five (5) portfolios formed per criteria of Warren Buffet has negative values in every period except in the first semester period in 2013, while the portfolio performance formed based on retained earnings (RORE) and based on LQ45 index is negative in every period. There is no difference between the portfolio performance which is formed based on every financial criterion according to Warren Buffet’s strategy and the stock portfolio performance which is formed based on LQ45 index.
Keywords: Optimal portfolio, Markowitz’s method, Sharpe’s method, Warren Buffet’s strategy, LQ45 index